Dilema Tata Kelola Pengungsi Global: Penanganan Illegal Maritime Arrivals (IMA) di Australia - Maing, Skolastika Genapang (Nation State: Journal of International Studies, 2020)
Australia as one of the countries that signed the Convention of Refugee 1951 has an obligation to apply principle of non-refoulement in the handling of refugees and asylum seekers entering its territory. However, the issue of national security and domestic turmoil caused Australia to continue use restrictive policies in dealing with refugees and asylum seekers, especially those who came by the sea (boat people) and did not have official documents. They are called Illegal Maritime Arrivals (IMA). Giving the term “illegal” causes no distinction between IMA and smuggling/trafficking criminals. This paper aims to explain the existence of dilemma in the management of refugees especially in Australia in handling IMA. This research uses qualitative methods with secondary data sources from books, journals, articles and other sources related to the problem being studied. By using the concept of securitization approach in the paradigm of constructivism, this paper argue that the restrictive policies adopted by Australia as a form of protection of national interests. Australia experiences a dilemma in applying the principle of non-refoulement and protecting its national interests. This is challenge in the management of global refugees.